Comparison of the effects of enteral feeding through the bolus and continuous methods on blood sugar and prealbumin levels in ICU inpatients - Shahriari, Mohsen (J Educ Health Promot, 2015)
BACKGROUND: Appropriate nutritional support is effective on achievement of expected outcomes in intensive care unit (ICU) patients. Although several studies have suggested different conclusions about the effectiveness of tube feeding methods, there is no specific program of nutritional support for patients who have been hospitalized. There is a possibility for complications due to an inadequate nutrition. The aim of our study is to compare the effects of enteral feeding through the bolus and continuous methods on blood sugar and prealbumin level among the ICU inpatients. MATERIALS AND METHODS: Fifty subjects were selected by convenient sampling from April to Aug 2013 in the ICU wards of Alzahra Hospital, Isfahan, Iran, and randomly assigned to study and control groups in this clinical trial. The subjects in the study group received infusion pump feeding while the control group received bolus feeding for 72 h. Blood sugar was checked for every 4 h for 72 h and the prealbumin level was assessed on the first and the fourth day in two groups. RESULTS: In the study group, the mean blood sugar significantly decreased on the fourth day, compared with the first (P = 0.03, F = 3.85) and third (P = 0.01, F = 3.15) day. In the control group, the mean blood sugar increased from the first day. It was significantly higher in the control group on the second day (P = 0.02, F = 3.55), compared with the study group. In the study group, there was a significant difference in the mean prealbumin before and after intervention (P = 0.048, t = 1.97), but no significant difference was observed in the control group. There was a significant difference between two groups after intervention (P = 0.04, t = 2.05). CONCLUSION: The obtained results showed that supportive nutrition through a continuous method had an effect on critical patients’ blood sugar control and made a better nutritional status for these patients through an increase of prealbumin level. Positive effects of this feeding method can result in appropriate outcomes for patients’ recovery and reduce the complications.